2019
DOI: 10.1371/journal.pone.0213527
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondrial DNA: New indices of type 2 diabetes-related cognitive impairment in Mexican Americans

Abstract: Mitochondrial function has been implicated and studied in numerous complex age-related diseases. Understanding the potential role of mitochondria in disease pathophysiology is of importance due to the rise in prevalence of complex age-related diseases, such as type 2 diabetes (T2D) and Alzheimer’s disease (AD). These two diseases specifically share common pathophysiological characteristics which potentially point to a common root cause or factors for disease exacerbation. Studying the shared phenomena in Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…In this context, circulating mtDNA is increasingly acknowledged as a pivotal mediator linking mitochondrial dysfunction to inflammation [30,34,35]. Of all mitochondrial components, mtDNA is the most susceptible to be sensed as a "non-self" molecule due to the presence within its structure of aberrant/devoid CpG methylation motifs that can trigger inflammation [34][35][36][37][38][39][40]. Fragmented mtDNA as well as circular double-stranded or linear single-stranded mtDNA molecules and nucleoids have been found in the human plasma in various disease conditions [37,38,[41][42][43].…”
Section: Failing Mitochondrial Quality Control and Mtdna Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, circulating mtDNA is increasingly acknowledged as a pivotal mediator linking mitochondrial dysfunction to inflammation [30,34,35]. Of all mitochondrial components, mtDNA is the most susceptible to be sensed as a "non-self" molecule due to the presence within its structure of aberrant/devoid CpG methylation motifs that can trigger inflammation [34][35][36][37][38][39][40]. Fragmented mtDNA as well as circular double-stranded or linear single-stranded mtDNA molecules and nucleoids have been found in the human plasma in various disease conditions [37,38,[41][42][43].…”
Section: Failing Mitochondrial Quality Control and Mtdna Releasementioning
confidence: 99%
“…Via these structures, mtDNA nucleoids (i.e., mtDNA complexed with the mitochondrial transcription factor A) can be displaced into the cytosol [ 37 , 38 , 65 ]. Altered mitochondrial dynamics have also been associated with mtDNA-driven inflammation [ 34 , 35 , 36 , 39 , 40 ]. In particular, preclinical models of optic atrophy 1 ablation and dynamin related protein 1 (Drp1) overexpression show hyper-fragmented mitochondria and giant mtDNA nucleoids outside of mitochondria that are able to trigger an immune response [ 66 ].…”
Section: Mitochondrial Quality Control Mtdna Release and Inflammmentioning
confidence: 99%
“…This result supports the importance of measuring both cellular and cell-free mtDNA-if only cellular content had been measured the alteration in the cf levels would have been missed. Several studies have quantified circulating mtDNA in diabetic patients to evaluate its potential as a biomarker, particularly in the development of various complications associated with diabetes 13,26,55,56 and higher levels of mtDNA have been previously reported in plasma of patients with diabetes compared to healthy controls. 13,56 Similarly to our findings, Silzer et al 55 reported differing trends in cellular and cf mtDNA in their study of type 2 diabetes and cognitive dysfunction; plasma mtDNA content increased only in T2D patients with cognitive impairment, while the buffy coat mtDNA content was altered with cognitive impairment regardless of diabetes status.…”
Section: T a B L E 3 Circulating Mtdna Content Of Diabetes Patientsmentioning
confidence: 99%
“…There are several preliminary studies that suggest this might be a useful approach ( Mengel-From et al 2014 ; Silzer et al 2019 ), with the caution that the relation between mtDNA copy number measured in peripheral cells (e.g., white blood cells) in many of these studies and mtDNA copy number in brain cells is not well understood. In the larger of these studies ( N = 1067), Mengel-From et al found steady mtDNA copy numbers through age 48 years in healthy individuals and age-related declines thereafter.…”
Section: Empirical Studies and Testing The Hypothesismentioning
confidence: 99%
“…For older individuals, higher mtDNA copy numbers were associated with better physical health and higher cognitive performance; “higher mtDNA copy number was consistently associated with higher cognitive composite score and MMSE [Mini Mental State Examination]” ( Mengel-From et al 2014, p. 1152 ). In a sample of older women, J. W. Lee et al ( 2010 ) found that higher mtDNA copy number was associated with higher MMSE scores ( r = 0.33), controlling age and years of education, and Silzer et al ( 2019 ) found that higher copy number was associated with better list learning and memory scores in older adults ( r = 0.46).…”
Section: Empirical Studies and Testing The Hypothesismentioning
confidence: 99%